Students with disabilities in higher education call for personal empowerment, equitable inclusive systems, and individualized accommodations - Bartolo, Paul A.; Borg, Michelle; Callus, Anne-Marie; Camilleri, Liberato; De Gaetano, Alistair; Mangiafico, Marchita; Mazzacano D'Amato, Edward; Sammut, Carmen; Vidal, Ramona Vella; Vincent, Jonathan (Frontiers in Education, 2025)
IntroductionThe number of students with disabilities in higher education is increasing, but research shows that they continue to face significant challenges for equitable participation. This study aims to deepen our understanding of these challenges through the perceptions of students with disabilities themselves.MethodsParticipants were students with disabilities enrolled at the University of Malta. Data was collected through a student survey with quantitative and open-ended questions and semi-structured interviews with students on their aspirations, on how far they felt enabled to participate in the university academic and social environments, and on how useful were the individual accommodations provided for their equitable participation. The online questionnaire was completed by 51 students constituting 21% of the total relevant population, while four semi-structured interviews were held with autistic students.ResultsThe findings firstly showed that these students considered the university as mainly an opportunity for self-development but experienced significant difficulties during their transition to and at the university for developing a healthy self-identity in the ableist university environment. Secondly, students called for the teaching system to be more pedagogically effective and sensitive to diverse student needs and for their involvement in the development of appropriate facilities for students. Thirdly, they reported that individual accommodations were necessary for their equitable participation and called for less bureaucratic processing of applications, individual negotiation of accommodations, and a system for informing lecturers of students' needs.DiscussionThe study suggests that higher education institutions should listen to the concerns of students with disabilities and involve them in curricular and environmental planning. They need to create a diversity respectful ethos and socio-emotional support that promotes everyone's membership in the university community, while adopting a universal design for learning mindset that is open to the diverse needs of students and providing a smooth system of accommodations for other individual needs.